Retrospective analyses of factors influencing arrhythmias and the impact of arrhythmias on inpatient outcomes among hospitalized patients with hemochromatosis. (1st April 2022) - Jackson, Inimfon; Oyenuga, Mosunmoluwa; Balogun, Omotola; Oyenuga, Abayomi; Etuk, Aniekeme; Jackson, Nsikak
Abstract: Background: Though hemochromatosis is described as an infiltrative cardiomyopathy that can result in arrhythmias, studies are lacking on the impact of arrhythmias in this population. We examined the prevalence, factors influencing arrhythmias, and impact of arrhythmias on inpatient outcomes among hospitalized patients with hemochromatosis. Methods: Retrospective cohort analyses were conducted using data from the National Inpatient Sample (NIS) collected between 2016 and 2018. Descriptive analyses were done to assess the prevalence of arrhythmias in patients with hemochromatosis. Univariate and multivariable logistic and linear regression models were used to examine the factors associated with arrhythmias and hospital-associated outcomes among patients with hemochromatosis. Results: 11.7% of hemochromatosis patients were diagnosed with arrhythmias. Compared to hemochromatosis patients less than 40 years old, those between 40 and 59 years had 2.3 times higher odds (Adjusted Odds Ratio (AOR): 2.35; 95% Confidence Interval (CI): 1.81–3.05) of having arrhythmias relative to no arrhythmias while patients aged 60 and above had 5 times higher odds (AOR: 4.96; 95% CI: 3.74–6.58) of arrhythmias. Compared to male patients, females were significantly less likely to be diagnosed with arrhythmias. Hispanics were 36% (AOR: 0.64; 95% CI: 0.47–0.86) less likely to have arrhythmias when compared to their non-Hispanic white counterparts. Other factors associated with arrhythmias were income, insurance type, and patient disposition. Furthermore, arrhythmias were related to higher hospital mortality, longer hospital stays, and total hospital charges. Conclusion: Our findings accentuate the need for close monitoring and early detection of arrhythmias in patients with hemochromatosis to improve their health outcomes. Patients need to be continually educated on their medical diagnoses and the need for treatment adherence, while hospitalist physicians need to ensure good continuity of care between the hospital and primary care setting to drive hospital costs down while keeping patients healthy. Highlights: 11.7% of hemochromatosis patients also have a diagnosis of arrhythmias. Age, gender, income, insurance type and patient disposition are associated with a diagnosis of arrhythmias. Arrhythmias are related to higher hospital mortality, longer hospital stays and total hospital charges.